HERMENEUTIC ANALYSIS OF HADITH IHSAN TOWARD A THEOPHANIC CONSCIOUSNESS IN TARBIYYAH WUJUDIYYAH - Deva Musthofal Hamdi; Elan Sumarna; Cucu Surahman (Senarai: Journal of Islamic Heritage and Civilization, 2026)
This study reconstructs the understanding of the ḥadīth of iḥsān as a philosophical foundation for Prophetic Theophanic Consciousness and its implications for Tarbiyyah Wujūdiyyah, an ontological approach to Islamic education. Previous studies have predominantly interpreted the ḥadīth of iḥsān within ethical, legal, and devotional frameworks, while giving comparatively limited attention to its ontological significance and its pedagogical implications for reconstructing human consciousness. This study therefore examines the ḥadīth of iḥsān as an interpretive tradition through which the relationship between prophetic consciousness, Divine self-disclosure (tajallī), and human formation may be philosophically reconstructed. The study employs a philosophical hermeneutic inquiry grounded in Amin Abdullah's integrative-interconnected epistemological paradigm. The analytical process combines hadith criticism, Gadamerian philosophical hermeneutics, theophanic phenomenology developed by Henry Corbin and Michel Henry, and William Chittick's ontological interpretation of Ibn ʿArabī's metaphysics. Following Wael Hallaq's distinction between historical inquiry and normative-philosophical reasoning, the study differentiates the historical authenticity of religious narrations from their philosophical interpretation. The analysis suggests that iḥsān may be understood not merely as an ethical obligation but also as an ontological mode of consciousness through which human beings cultivate awareness of Divine presence. Based on this interpretation, the study offers Prophetic Theophanic Consciousness as a conceptual framework for interpreting the existential dimensions of Islamic education and discusses its implications for the reconstruction of Tarbiyyah Wujūdiyyah. Rather than presenting a definitive theological model, this study contributes an interpretive framework that remains open to further philosophical, historical, and empirical inquiry within contemporary Islamic educational scholarship.